The European Convention on Human Rights and general international law - Aaken, Anne van; Motoc, Iulia (Oxford : Oxford University Press, 2018)
This text explores the interaction, divergence, and convergence between the European Court of Human Rights and general international law as developed by the International Court of Justice. It focuses on sources of international law, methods of interpretation, jurisdiction, state responsibility, and immunity.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 25, 2018).
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); European Court of Human Rights; International Court of Justice; International law and human rights; Law; International law